IMPLEMENTASI PROGRAM PELATIHAN PEMBERDAYAAN PEREMPUAN BERBASIS ILMU PENGETAHUAN DAN TEKNOLOGI (IPTEK) - Prasetyo, Andjar; Asmara, Anugerah Yuka (Jurnal Ilmu Administrasi Negara, 2013)
Sea topographyin Lingga regency contains marine and fishery endowment much, which has not been utilisedoptimally. This study is a descriptive-qualitative approach aiming to elaborate the effort of BadanPemberdayaan Perempuan, Perlindungan Anak dan Keluarga Berencana (BP3AKB) KabupatenLingga in initiating creation the number of 15 communities of women empowerment based onscience and technology. BP3AKB involves an inovator of newsqita from Magelang Town in assistingthe woman community to optimize the marine potency and to address the ecological issues inLingga area. Practically, the communities of women empowerment arrange their rules and to coordinateeach others in applying newsqita in their environment. As a result, newsqita is capable to improvethe society welfare and to address the ecological issues in Lingga area.Key words: women empowerment community, society welfare, appropriate technology.